fNIRS-based evaluation of the impact of SARS-CoV-2 infection central auditory processing - Yaman, Handan; Yılmaz, Oğuz; Hanoğlu, Lütfü; Bayazıt, Yıldırım (Wiley, 2023)
ObjectivesCoronavirus disease-2019 due to SARS-CoV-2 infection has been associated with neurological and neuropsychiatric illnesses as well as auditory system problems. In this study, we aimed to evaluate the impact of SARS-CoV-2 infection on the central auditory system by assessing the hemodynamic activation changes using functional near-infrared spectroscopy (fNIRS).MethodsThree participants who had SARS-CoV-2 infection (study group) and four participants who had no SARS-CoV-2 infection (control group) were included in the study. During the auditory oddball task in which two different frequencies of tonal stimulation were presented at 80 dB HL, the participants were asked to pay attention to the rare tonal stimulation and mentally count these target stimuli throughout the task. During this task, oxygenated hemodynamic response functions were evaluated with fNIRS.ResultsSignificantly increased oxygenated hemodynamic responses were observed in both groups during the task (p < .05), which was significantly higher in the study group (p < .05). Significantly more HbO activation was observed in the vmPFC, superior temporal gyrus, and medial temporal gyrus in the study group compared to controls (p < .05). Significantly higher hemodynamic activation was observed in the right hemisphere in both groups, which was significantly higher in the study group (p < .05).ConclusionSARS-CoV-2 infections may impact on central auditory processing or auditory attention due to changes in oxyhemoglobin levels in the frontal and temporal brain regions. It seems that SARS-CoV-2 infection is associated with an additional load on neural activity, and difficulties in focusing in auditory attention, following speech and hearing in noise as well as increased effort to perceive auditory cues.
Keywords: Auditory Attention; fNIRS; Oddball Paradigm; SARS-CoV-2